ANALYSIS OF JOB TRAINING, WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT CLASS II A CORPORATE INSTITUTIONS, BATAM CITY - Ismoyo, Riky; Indrayani, Indrayani; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
Performance of employees is important thing _ in something organization / agency . The capabilities possessed by the source power man naturally no free from a number of factor important pusher . Purpose study this is for knowing influence training work , motivation work and culture organization to performance employee at the Class II A Penitentiary of Batam City . Analysis used _ that is analysis associative , trait study this is quantitative , analysis multiple linear regression and analysis coefficient determination with use IBM SPSS 22 program assistance . Population in study this is whole employee institution correctional class II A Batam City , while the sample is with use formula slovin so obtained 95 respondents . Results obtained from study this showing that : 1) Training Work take effect significant by Partial on Employee Performance in Class II A Penitentiary in Batam City , 2 ) Motivation Work take effect significant by Partial on Employee Performance in Class II A Correctional Institutions in Batam City , 3) Culture Organization take effect significant by Partial on Employee Performance in Class II A Correctional Institutions in Batam City , 4) Training Work , Motivation Work and Culture Organization take effect significant by simultaneous on Employee Performance in Class II A Penitentiary in Batam City . Adjusted R square value 0, 699 could called coefficient determination , thing this means 0, 699 (69, 9 %) Employee Performance could obtained and explained by Training Work , Motivation Work and Culture Organization whereas the rest by 31.1% explained by variable outside the model that is not researched.